Micro-system aquaponics: testing designs for increased productivity. Issue 2 (2nd April 2020) - Adams, Brittney; Boyer, Tyan; Albrecht, Marc; Ranglack, Dustin H.; Bickford, Nate
ABSTRACT: The objective of these six experiments (single species vs multispecies, filter vs no filter, gravel bottom vs glass bottom, heaters vs no heaters, gravel vs clay substrate and commercial feed vs custom-made feed) was to gain an understating of how manipulating variables would affect the fish, biomass, and nutrient dynamics. Each experimental designed used 37.9-l tank, there were five control tanks and five experimental tanks for each variable tested. Nutrient reading (NO3-and NH4+), water chemistry variable (pH and dissolved oxygen (DO)), fish health, production weight (fruits and biomass) were taken throughout the six-month time span. The data indicate the best management in an aquaponics system. Several significant relationships were found in the experiments that related to differences in ammonium processing into nitrate. There was a significant difference in NO3 − in four of the six experiments. With the exception of the tank substrate experiment, plant biomass was not significantly different between treatments. Most likely there was a limiting factor in growth not measured. However, we are still able to recommend some designs ingredients for a small aquaponics system that could translate into larger systems. We recommend systems to include added mechanical filtration and gravel bottom in fish tanks. This will add a greater surface area for bacterial growth.